2007
DOI: 10.1002/ijc.23319
|View full text |Cite
|
Sign up to set email alerts
|

Fruit and vegetable intake and head and neck cancer risk in a large United States prospective cohort study

Abstract: Squamous head and neck cancers include cancers of the oral cavity, pharynx and larynx are the sixth leading cause of cancer mortality worldwide, resulting in more than 350,000 deaths annually. Intake of fruit and vegetables may protect against head and neck cancer incidence, although few prospective studies have examined this association. We investigated this relation in 490,802 United States participants of the NIH-AARP Diet and Health cohort using Cox proportional hazard models adjusted for potential confoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
152
3
6

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 201 publications
(169 citation statements)
references
References 20 publications
8
152
3
6
Order By: Relevance
“…General characteristics of case-control and cohort studies are shown in Tables 1 and 2, respectively. Case-control studies were published between 1994 and 2014; three were conducted in Italy (13,19,22) , two each in Iran (10,15) , China (12,23) and Australia (14,29) , and one each in Poland (16) , Spain (11) , Czech Republic (17) , Brazil (18) , UK (20) , India (24) , Hawaii (25) , Mexico (26) , Sweden (27) and Uruguay (28) . One was a multinational study conducted in nine countries worldwide (Italy, Spain, Poland, Northern Ireland, India, Cuba, Canada, Australia and Sudan) (21) Cohort studies were published between 1998 and 2012; nine were conducted in the USA (30,31,(34)(35)(36)(37)39,40,45) and eight were conducted in Europe (32,33,38,(41)(42)(43)(44)46) . Pooled analysis were conducted in the USA, Canada, Europe and Australia and included from seven to fourteen prospective studies (47)(48)(49)(50) .…”
Section: Literature Searchmentioning
confidence: 99%
“…General characteristics of case-control and cohort studies are shown in Tables 1 and 2, respectively. Case-control studies were published between 1994 and 2014; three were conducted in Italy (13,19,22) , two each in Iran (10,15) , China (12,23) and Australia (14,29) , and one each in Poland (16) , Spain (11) , Czech Republic (17) , Brazil (18) , UK (20) , India (24) , Hawaii (25) , Mexico (26) , Sweden (27) and Uruguay (28) . One was a multinational study conducted in nine countries worldwide (Italy, Spain, Poland, Northern Ireland, India, Cuba, Canada, Australia and Sudan) (21) Cohort studies were published between 1998 and 2012; nine were conducted in the USA (30,31,(34)(35)(36)(37)39,40,45) and eight were conducted in Europe (32,33,38,(41)(42)(43)(44)46) . Pooled analysis were conducted in the USA, Canada, Europe and Australia and included from seven to fourteen prospective studies (47)(48)(49)(50) .…”
Section: Literature Searchmentioning
confidence: 99%
“…[44]. Cette revue citait deux études de cohorte rapportant des risques relatifs de 0,6 (IC à 95 % : 0,37-0,99) [45] et de 0,7 (IC à 95 % : 0,55-0,92) [46], pour une consommation de fruits et de légumes importante (7,7 et 5,8 portions par jour respectivement) par rapport à une consommation faible (1,5 et 2,5 portions par jour). La consommation de café n'était pas associée à la survenue de cancer en général et elle a même plutôt été décrite comme pouvant prévenir certains cancers (endomètre, sein, colon, rectum) [47].…”
Section: Discussionunclassified
“…They contain the carotene lycopene, one of the most powerful natural antioxidants. In some studies, lycopene especially in cooked tomatoes has been found to help prevent prostate cancer [12]. But other research contradicts this claim [26].…”
Section: Introductionmentioning
confidence: 99%
“…The richest source of lycopene in the diet is tomato and tomato derived products [20]. Tomato consumption has been associated with decreased risk of breast cancer [30] head and neck cancers [11] and might be strongly protective against neurodegenerative diseases [12,26].Tomato sauces and puree are said to help lower urinary tract symptoms (BPH) and may have anticancer properties [28]. Tomato consumption might be beneficial for reducing cardiovascular risk associated with type 2 Diabetes [24].…”
Section: Introductionmentioning
confidence: 99%